Journalism, Ethics, Mobilities and Transmedia Narratives - SILVA [Editor Convidado], Fernando Firmino da (2016)
In this issue [V.3, N.2] the Latin-Aerican Journal of Journalism – Ancora, brings together a series of articles in order to reflect on the complexities of contemporary journalism, from ethical issues, new construction accounts, and mobility in the spheres of consumption and journalistic production. Supported in coming articles of the International Symposium on Journalism Multiplatform environments - held in November 2015 in the city of João Pessoa, at the initiative of the Research Group in Journalism, Media, Accessibility and Citizenship - RGJMAC, linked to Journalism Graduate Program UFPB, and the Research Group on Journalism and Mobility – RGJM, of the State University of Paraíba; plus articles received continuous flow to the Thematic Forum.DOI: 10.21204/2359-375X/ancora.v3n2p9-13